Lymphangioleiomyomatosis in lymph node cytology: Another "Floating Island" to visit. Issue 6 (28th March 2023) - Jawaid, Tabinda; Swanson, Amy A.; Bois, Melanie C.; Folpe, Andrew L.; Rivera, Michael; Hartley, Christopher P.; Sturgis, Charles D.
Abstract: Lymphangioleiomyomatosis (LAM) is a rare disease with variable presentations. The neoplastic cells in LAM demonstrate a unique and diagnostically important "myomelanocytic" phenotype. Cytologic reports of LAM are infrequent and have not in the past emphasized the floating island pattern in which circumscribed aggregates of lesional cells are rimmed by appliques of flattened endothelium. This case illustrates the cytology of LAM and emphasizes that the floating island cytoarchitectural pattern more classically associated with entities such as hepatocellular carcinomas may be seen in cytological preparations of LAM at unanticipated body sites.